Erenumab in the prevention of high‐frequency episodic and chronic migraine: Erenumab in Real Life in Italy (EARLY), the first Italian multicenter, prospective real‐life study. Issue 2 (18th December 2020) - Barbanti, Piero; Aurilia, Cinzia; Egeo, Gabriella; Fofi, Luisa; Cevoli, Sabina; Colombo, Bruno; Filippi, Massimo; Frediani, Fabio; Bono, Francesco; Grazzi, Licia; Salerno, Antonio; Mercuri, Bruno; et al.
Abstract: Objective: To assess the effectiveness, safety, and tolerability of erenumab in a real‐life migraine population, while trying to identify responsiveness predictors. Background: Erenumab is a fully human Ig‐2 monoclonal antibody blocking the calcitonin gene‐related peptide receptor, indicated for migraine prophylaxis. Phase II and III trials demonstrated that erenumab is effective, safe, and well tolerated in the prevention of episodic and chronic migraine (CM), showing an early onset of action. Methods: This is a multicenter, prospective, cohort, and real‐life study. We considered for enrolment all consecutive patients aged 18–65 affected by high‐frequency episodic migraine (HFEM) or CM, with or without medication overuse, visited at nine Italian Headache Centers from December 20, 2018 to September 30, 2019. Each patient was treated with erenumab 70 mg, administered subcutaneously every 4 weeks. Treatment duration was planned to last from 6 to 12 months, depending on the patient's response. The primary endpoint was the change in monthly migraine days (MMDs) at weeks 9–12 compared to baseline. Secondary endpoints included changes in monthly analgesics intake, ≥50%, ≥75%, and 100% responder rates and any variation in the Visual Analog Scale (VAS) and Headache Impact Test scores (HIT). Results: In total, 372 migraine patients were treated with at least one dose of erenumab 70 mg. At weeks 9–12, erenumab decreased MMDs by 4.5 ± 4.1 days (mean ± SD) in patients with HFEM and by 9.3 ± 9.1 (mean ± SD) days in those with CM compared to baseline. At weeks 9–12 VAS score was reduced by 1.9 ± 1.9 (mean ± SD), HIT score by 10.7 ± 8.8 (mean ± SD), and median monthly analgesics intake passed from 12.0 (interquartile range [IQR] 10.0–14.0) to 5.0 (IQR 3.0–7.0) in HFEM. In CM patients, VAS was reduced by 1.7 ± 2.0 (mean ± SD), HIT by 9.7 ± 10.4 (mean ± SD), and median monthly analgesics intake passed from 20.0 (IQR 15.0–30.0) to 8.0 (IQR 5.0–15.0). At week 12, ≥50% responders were 60/101 (59.4%) for HFEM and 146/263 (55.5%) for CM, ≥75% responders were 17/101 (16.8%) and 59/263 (22.4%) and 100% responders 1/101 (1.0%) and 3/263 (1.1%), respectively. Erenumab responsiveness in HFEM was positively associated with unilateral pain localization (OR: 3.03, 95% CI: 1.24–7.40; p  = 0.015), whereas in CM responsiveness was positively associated with and baseline migraine frequency (OR: 1.06, 95% CI:1.02–1.11; p  = 0.031), dopaminergic symptoms (OR: 2.01, 95% CI: 1.14–3.52; p  = 0.015), and negatively associated with psychiatric comorbidities (OR: 0.43, 95% CI: 0.20–0.93; p  = 0.003). Conclusions: Erenumab 70 mg is effective, safe, and well tolerated in real life. Easily obtainable clinical features might be of help in predicting patient's responsiveness.